Clinical and laboratory manual of dental implant abutments - Shafie, Hamid R. (Ames, Iowa : John Wiley & Sons Inc., 2014)
'To fulfill the vision for his latest book, Dr. Shafie compiled an immense amount of technical information from a vast variety of sources, including implant manufacturers and designers, master dental technicians, implant researchers, and expert clinicians leading the field of implant dentistry worldwide. He and his expert contributors meticulously assembled each chapter to include only the most relevant and up-to-date content and procedures in a concise and simple format that even the most novice clinician can comprehend. Dr. Shafie follows the same easy-to-read, easy-to-understand format as his best-selling textbook Clinical and Laboratory Manual of Implant Overdentures. Starting with the material science behind implant abutments, Dr. Shafie then describes all of the relevant abutment solutions, providing a step-by-step guide to design and manufacturing of the CAD/CAM abutments and explaining how to adjust prefabricated abutments and one-piece titanium and zirconia implants. In addition to offering the ultimate procedural guide for clinical and laboratory preparation of dental implant abutments, this textbook is filled with useful tips on clinical practice management such as sterilization, instrumentation and trouble-shooting related to implant abutments. With more than 500 high-quality pictures and illustrations, it is the most complete and authoritative resource on implant abutments available. Clinical and Laboratory Manual of Dental Implant Abutmentsis the only text devoted exclusively to an in-depth look at implant abutments. Every dental implant clinician, technician, student, and implant industry insider needs this vital work in their library'--Provided by publisher.
Machine generated contents note: Clinical and Laboratory Manual for Dental Implant Abutments Chapter 1) Implant Abutment materialsHamid R. Shafie and Bryan A. White Chapter 2) General information about implant abutmentsHamid R. Shafie Chapter 3) Retaining abutment screwHamid R. Shafie and Scott Martyna Chapter 4) Different implant abutment connections Hamid R.Shafie and Bryan A. White Chapter 5) Prefabricated implant abutmentsPaul P. Binon Chapter 6) The use of CAD-CAM Technology in Implant Custom Abutment ManufacturingJulian Osario and Robert B. Kirstein Chapter 7) Relationship between abutment geometry and peri-implant tissue in the esthetic zone casesDean Morton Chapter 8) Instrumentation for abutment modification and guidelines to uses Hamid R. Shafie Chapter 9) Abutment preparation technique for one-piece titanium ad zirconia implantsHamid R. Shafie and Mary L. Ballard Chapter 10) Cleaning, disinfection and sterilization instruction implant abutments.
Includes bibliographical references and index.
Keywords: Dental Abutments; Dental Implant-Abutment Design